Exploiting Opportunistic Scheduling Schemes on Cooperative NOMA Networks Under Active Eavesdropper - Kyusung Shim; Soo-Hyun Park; Byung-Seo Kim; Beongku An (IEEE Access)
In this paper, we investigate secure transmission in a cooperative non-orthogonal multiple access (NOMA) system in the presence of an active eavesdropper. To enhance secrecy performance, we propose two approaches. The first is a novel cooperative NOMA architecture, in which the cell-edge user generates a jamming signal to degrade the eavesdropper’s channel condition. The second is a novel opportunistic scheduling scheme, referred to as the minimum antenna selection (MAS) scheme, which selects the transmit antenna at the source node to minimize the maximum eavesdropper channel capacity between the cell-center and cell-edge users. We derive closed-form expressions for the secrecy outage probability (SOP) of both the cell-center and cell-edge users to characterize the impact of various network parameters on secrecy performance. Through numerical results, we analyze the impact of the source, cell-center, and cell-edge users’ transmit power on the SOP; the impact of the power allocation coefficient, target secrecy rate, and eavesdropper transmit power on the total SOP; and the impact of the distance between the source node and the eavesdropper, as well as the distance between the cell-center user and the eavesdropper, on the secrecy sum throughput (SST). These results demonstrate that the proposed cooperative NOMA architecture and the MAS scheme can effectively protect confidential messages against active eavesdropping attacks.